A review on metal additive manufacturing for intricately shaped aerospace components - Madhavadas, Vaishnav; Srivastava, Divyansh; Chadha, Utkarsh; Raj, Sakthivel Aravind; Sultan, Mohamed Thariq Hameed; Shahar, Farah Syazwani; Md Shah, Ain Umaira (Elsevier, 2022)
Additive manufacturing (AM) is one of the fastest-growing industrial techniques, bringing many innovative solutions to different manufacturing problems. In AM, a sliced image of the 3D model is layered together to make a 3D object. The main reason for the exponential growth of AM is its numerous advantages over conventional methods, such as high-cost efficiency, less material wastage, a very high degree of freedom, and lesser material constraints. One of the biggest contributors to this growth is the aerospace industry. It is due to the ease of making complex structures and alloys with a very high strength-to-weight ratio (S:W). The authors have comprehensively reviewed the use of AM in the aerospace industry in this review. This review mainly focuses on the metal AM of complex components used in the Aerospace industry. The other topics in this review are an in-depth study of the different AM techniques, a classification of different AM processes, a comparison between conventional and AM techniques, an advantage of AM techniques, and the future scope of AM techniques. The material characterization and microstructure of the components and the different process parameters concerning the cost and irrespective of cost are also briefly discussed.